Accounting employability: a systematic review of skills, challenges, and initiatives - Yutong Nie; Nor Hamimah Mastor (Cogent Business & Management, 2024)
This systematic literature review examines the current state of accounting employability research, focusing on required skills, challenges, and initiatives to enhance graduate preparedness. Following PRISMA guidelines, 45 relevant studies were analysed. Key findings highlight the growing importance of a diverse skill set for accountants, including professional skills, soft skills, digital skills and strategic competencies. Meanwhile, a significant gap remains between employer expectations and graduate competencies. The review identifies several initiatives to bridge this gap, such as work-integrated learning and curriculum reforms. The study also highlights barriers to implementation, including limited resources, the need for faculty development, and challenges in engaging students. It suggests directions for future research, recommending efforts that focus on policy development, teacher motivation, curriculum improvements, and student engagement to strengthen accounting education and enhance graduate employability. This review provides insights for accounting practitioners, accounting students, educators, employers, and policymakers to enhance accounting education and improve employability in a rapidly evolving professional landscape.
Keywords: 650; accounting employability; higher education; curricula; professional development; education for sustainable development